Radiotherapy Can Cause Haemostasis in Bleeding Skin Malignancies - Helena Sung-In Jang; Andrew Spillane; Frances Boyle; Gerald Fogarty (Case Reports in Medicine)
Radiotherapy (RT) can cause haemostasis in select cases of malignant bleeding. We present two cases where RT was used to prevent fatal exsanguination from bleeding skin malignancies. Treatment was with radical intent in one case and palliative intent in the other. The dose used in both cases was 20 Gray (Gy) in 5 fractions. To our knowledge, this is the first report of radiation-induced haemostasis in bleeding skin malignancies.